Captivity beyond prisons : criminalization experiences of Latina (im)migrants - Escobar, Martha D. (University of Texas Press, 2016)
"Escobar examines the criminalization of Latina (im)migrants, delving into questions of reproduction, technologies of power, and social justice in a prison system that consistently devalues the lives of Latinas."--Publisher's description